Monetary dynamics in the euro area: a disaggregate panel approach - J. Liu; Clemens J. M. Kool (Utrecht University, Utrecht University School of Economics, Tjalling C. Koopmans Research Institute, 2017)
In this paper, we use panel cointegration estimation to analyze the determinants of heterogeneous monetary dynamics in ten euro area member countries over the period 1999-2013. In particular, we investigate the role of real house prices, real equity prices and cross border bank credit. For the period up till 2008 we find a significantly positive income effect, a significantly negative interest rate effect, a significantly negative effect of net foreign credit and a significantly positive housing price effect. Inclusion of the financial crisis shows evidence of a structural break in money demand and some sign reversals, most significantly so for the interest rate effect. Finally, we find evidence of a divide in the long-term money demand relation between the Northern and Southern parts of the euro area, potentially complicating monetary policy.
Keywords: 330; money demand stability; structural breaks; panel cointegration; DOLS; asset prices; net foreign credit